2019
DOI: 10.1016/j.canlet.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulat-INGs in tumors and diseases: Focus on ncRNAs

Abstract: ING family genes (Inhibitor of Growth) are tumor suppressor genes that play a vital role in cell homeostasis. It has been shown that their expression is lost or diminished in many cancers and other diseases. The main mechanisms by which they are regulated in oncogenesis have not yet been fully elucidated. The involvement of non-coding RNAs (ncRNAs) and in particular microRNAs (miRNAs) in post-transcriptional gene regulation is well established. miRNAs are short sequences (18 to 25 nucleotides) that can bind to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 145 publications
(174 reference statements)
0
10
0
Order By: Relevance
“…Consistently, studies also reported that ING2 was downregulated at the mRNA level in lung cancer cell lines [49,50]. Nevertheless, contradictory results have been found when analyzing TCGA and The Human Protein Atlas (THPA) databases, as the authors did not find any correlation between INGs mRNA and protein expression [52]. It is worth noticing that ING2 degradation has been shown to be mediated by Smad 1 ubiquitination regulatory factor 1 (Smurf 1) [65], a protein highly expressed in lung cancer [66].…”
Section: Ing2 Status In Human Tumorsmentioning
confidence: 71%
See 1 more Smart Citation
“…Consistently, studies also reported that ING2 was downregulated at the mRNA level in lung cancer cell lines [49,50]. Nevertheless, contradictory results have been found when analyzing TCGA and The Human Protein Atlas (THPA) databases, as the authors did not find any correlation between INGs mRNA and protein expression [52]. It is worth noticing that ING2 degradation has been shown to be mediated by Smad 1 ubiquitination regulatory factor 1 (Smurf 1) [65], a protein highly expressed in lung cancer [66].…”
Section: Ing2 Status In Human Tumorsmentioning
confidence: 71%
“…On the other hand, one publication suggested that the ING2 gene could be targeted on its 3′-UTR site by miR-8084, which showed tumor-promoting properties in breast cancer [51]. This post-translational regulation of the ING2 gene expression might explain the discrepancies observed in many publications between ING2 mRNA level and ING2 protein expression [52].…”
Section: Ing2 Status In Human Tumorsmentioning
confidence: 99%
“…These proteins are considered type II tumor-suppressor proteins since they are frequently downregulated in different cancers but are infrequently mutated [7,16]. They are also involved in several different biological processes, such as cell growth, senescence, apoptosis, and differentiation, due to their effects on chromatin remodeling [17,18,19,20,21].…”
Section: A Phd For Regulating Histone Acetylationmentioning
confidence: 99%
“…The miRNA, a single chain ncRNAs of around 22 nucleotides in length, influence the gene expression by binding to the 3′-UTR of their respective target genes [9]. They are key regulators that mediate tumor development and pathology, such as proliferation, transcription, post-transcriptional modifications, invasion, apoptosis, and cell metabolism [10]. However, the functions of lncRNAs and miRNA in gene expression regulation are not well characterized.…”
Section: Introductionmentioning
confidence: 99%